Adaptive event‐triggered resilient stabilization for nonlinear semi‐Markov jump systems subject to DoS attacks. (6th November 2022) - Lu, Lihui; Xia, Mengyuan; Qi, Wenhai; Yan, Huaicheng; He, Hangfeng; Cheng, Jun; Shi, Kaibo
Abstract: This article investigates the problem of adaptive event‐triggered resilient stabilization for nonlinear semi‐Markov jump systems with DoS attacks. In this article, both DoS attacks and event‐triggered transmission strategy (ETTS) are considered. The DoS attacks may disturb the event‐triggered strategy, which implies that the original inequality condition of ETTS will no longer be satisfied. Different from the traditional ETTS, the adaptive ETTS is designed to reduce bandwidth usage. Based on the adaptive ETTS and resilient controller, the sufficient condition for stochastic stability of the closed‐loop system is proposed. Then, the calculation method of controller and observer parameters is given in the form of linear matrix inequality. Finally, the proposed adaptive event‐triggered resilient controller is applied to a single‐link robot arm model, which can show effectiveness of the proposed method.